LEADERSHIP SUCCESSION IN THE NORTHERN GREAT PLAIN REGION – RESULTS OF A PILOT STUDY - Ivett STUMPF-TAMÁS; Marianna MÓRÉ (Oradea Journal of Business and Economics, 2025)
The aim of this study is to explore how the issue of leadership succession is evolving in the North Great Plain region among NGOs working with ageing populations. The research primarily examines current practices in filling leadership positions, organisational attitudes towards succession, and factors that hinder or facilitate organisational continuity. The study was carried out in the framework of a pilot study using quantitative methodological elements. The research instrument was a structured questionnaire, which was completed by a purposive sampling involving a total of 14 pensioner organisations. The research results show that, although the managers of the organisations interviewed generally have many years of professional and practical experience, succession processes are predominantly ad hoc and ad hoc. Organisational planning for leadership change is mostly absent, processes are not supported by formal documents and a strategic approach is rarely put into practice. Responses suggest that the issue of leadership succession is typically only addressed when the organisation is in a crisis situation, such as the retirement or unexpected departure of the current leader. This can be particularly problematic for civil society actors where organisational functioning is highly personalised and the role of the leader is decisive in day-to-day operational and strategic decision-making. The key leadership competences identified by respondents – in particular empathy, effective communication skills and the ability to think strategically – reflect the multidisciplinary and complex nature of the civil society leadership role. This underpins the need for not only management skills, but also a high degree of social and emotional intelligence and long-term planning skills to lead civil society organisations. The results of the research suggest that it is essential to create a supportive organisational and social environment that encourages conscious and forward-looking succession planning. In addition, ensuring the institutionalised transfer of leadership knowledge, experience and organisational values is of particular importance and can contribute to the long-term sustainability and effective functioning of retirement organisations. The study contributes to deepening the research discourse on leadership succession in the country, with a particular focus on the specific operating conditions, challenges and opportunities of rural organisations.